2014
DOI: 10.1590/1807-3107bor-2014.vol28.0001
|View full text |Cite
|
Sign up to set email alerts
|

Research in the field of health, dentistry, telehealth and teledentistry

Abstract: Research in the Field of Health, Dentistry, Telehealth and Teledentistry G lobal trends in Higher Education points, as guidelines to be pursued, lifelong learning, public accountability and the social dimension of higher education and research.The information and communication technologies (ICT) add a new dimension, influenced by the perception that the current society is globally interconnected, that our knowledge and our vision of the world is transitory, is always incomplete and reprocessing, that we can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…A low rate of utilization of teledentistry services provided to the oral health teams connected to the TelehealthRS project was observed. Haddad et al 7 note that it is still necessary to overcome barriers in the work process, in the incorporation of permanent education, and in the management of services to increase the use of telehealth and professionals' demand for teleconsultation services. Similar obstacles to the use of teledentistry have been reported in the literature with regard to issues of technical reliability, diagnostic accuracy, and the cost-benefit ratio of implementing teledentistry centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low rate of utilization of teledentistry services provided to the oral health teams connected to the TelehealthRS project was observed. Haddad et al 7 note that it is still necessary to overcome barriers in the work process, in the incorporation of permanent education, and in the management of services to increase the use of telehealth and professionals' demand for teleconsultation services. Similar obstacles to the use of teledentistry have been reported in the literature with regard to issues of technical reliability, diagnostic accuracy, and the cost-benefit ratio of implementing teledentistry centres.…”
Section: Discussionmentioning
confidence: 99%
“…6 This situation favours the use of new information and communication technologies (ICTs) aimed at improving professional qualifications and achieving greater equality in the provision of healthcare services. 7,8,9 Experiences in several countries have shown that investments in PHC made with the goal of improving physical resources and professional qualifications lead to a significant improvement in the population's health indicators. 10,11,12 The constant updating of scientific knowledge requires continued professional education to ensure the quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth has the potential to reduce time to diagnosis, 2 avoid unnecessary patient travel, optimize financial resources without compromising the quality of care, 3,4,5 and improve the resolution of care. 6 In general, telehealth has good acceptability by professionals and patients 5 , and enables better work conditions and less isolation of professionals working in remote areas, favoring their stay in these locations. 7 Teledentistry has growing applications in dentistry, increasing access and improving health services.…”
Section: Introductionmentioning
confidence: 99%
“…O Telessaúde é uma ferramenta de ensinoaprendizagem capaz de suprir as necessidades de conhecimento dos profissionais, contribuindo para efetivação do processo de EPS. A utilização de TIC proporciona uma percepção da sociedade atual, mostra a interligação global e promove o acesso contínuo e permanente a toda e qualquer informação 12 .…”
Section: Resultsunclassified